The International Gas and Crude Oil Price Variability Effect on Indonesian Coal Mining Companies Listed at IDX - Adi, Tri Wahyu (International Journal of Energy Economics and Policy, 2022)
This study investigates the influence of gas price, crude oil price and international coal demand on coal sales volume, coal selling price, coal sales revenue, financial performance, business risk and stock price Indonesia coal mining is listed on Indonesia Stock Exchange (IDX). The sample is Indonesia coal mining companies listed on IDX in the period 2014 – 2018. This study employs a structural equation model using GeSCA software to examine the relationship and effect between research variables. The empirical result shows that Crude Oil Price has a significant positive effect on Gas Price and International Coal Demand, bidirectionally. Gas Price has a significant negative effect on International Coal Demand, bidirectionally. International Coal Demand has no significant positive effect on Coal Selling Price and Sales Volume. Coal Selling Price has not a significant positive effect on Sales Volume. Production Cost has a significant positive effect on Coal Selling Price. Coal Selling Price and Sales Volume have a significant positive effect on Sales Revenue. Coal Sales Revenue has a significant negative effect on Enterprise Risk. The originality of this study investigates a relationship between International Coal Demand, Coal Selling Price and Coal Sales Volume which has never been done in previous research.